A review of the critical success factors of managing hotels in Vietnam (Ho Chi Minh). - Chan, Patricia Choy Mei. (2009)
The hotel industry is one important supporting pillar in any vibrant economy. Hotel establishments are staples in the physical infrastructure that generate employment and rake in tourist dollars. It is easy to be dazzled by the glamorous front and forget the grit and grime that go into the management. Investment amounts are huge, external environment is volatile, business partners are multi -- all these translate into a high degree of risk.